Pengaruh Penerapan Green Accounting dan Pengungkapan Corporate Social Responsibility (CSR) terhadap Nilai Perusahaan - Delvia, Selvina; Helmy, Herlina (Jurnal Eksplorasi Akuntansi, 2024)
This study aimed to determine the effect of implementing green accounting and Corporate Social Responsibility Disclosure on firm value. The research was conducted in Indonesia mining companies listed on the Indonesia Stock Exchange with an observation period of 2018-2022. The sampling methode used was purposive sampling, while the research sample consisted of 14 companies that had followed PROPER and were indexed on the IDX. The data analysis technique used is Multiple Linear Regression Analysis. The study results show that applying green accounting has no effect on firm value and Corporate Social Responsibility Disclosure has a positive effect on firm value.